Implementasi Metode AHP-MOORA dan AHP-SAW Pada Sistem Pendukung Keputusan Pemilihan E-Commerce Terbaik - Wahyuni, Sri; Nasution, Hamidah; Aprilia, Rima (Universitas Cokroaminoto Palopo, 2025)
Indonesia is currently experiencing very rapid technological development compared to a few years ago. The digital era marked by the 4.0 revolution affects every aspect of people's perceptions and purchasing power of an online store or online store which is often referred to as E-Commerce. 96% of internet users have searched for and purchased goods and services online. Of the various choices of E-Commerce in Indonesia, it sometimes makes the public as consumers confused in choosing the best and superior E-Commerce if it is based on several categories such as price, product variations, payment method variations, and so on to make transactions. To help make it easier for consumers to choose the best E-Commerce, an appropriate decision support system is needed. In this study, the implementation of the AHP-MOORA and AHP-SAW methods was used. The best E-Commerce is determined based on the weight of the criteria of 100 respondents who actively use E-Commerce. Stating that the “Shopee” alternative is the best E-Commerce with an AHP-MOORA preference value (rank) of 0.309 and AHP-SAW of 0.974. The